Comment on “Comparison of ozone measurement methods in biomass burning smoke: an evaluation under field and laboratory conditions” by Long et al. (2021) - N. Bernays; D. A. Jaffe; D. A. Jaffe; I. Petropavlovskikh; I. Petropavlovskikh; P. Effertz; P. Effertz (Atmospheric Measurement Techniques, 2022)
Long et al. (2021) conducted a detailed study of possible interferences in measurements of surface O3 by UV spectroscopy, which measures the UV transmission in ambient and O3-scrubbed air. While we appreciate the careful work done in this analysis, there were several omissions, and in one case, the type of scrubber used was misidentified as manganese dioxide (MnO2) when in fact it was manganese chloride (MnCl2). This misidentification led to the erroneous conclusion that all UV-based O3 instruments employing solid-phase catalytic scrubbers exhibit significant positive artifacts, whereas previous research found this not to be the case when employing MnO2 scrubber types. While the Long et al. (2021) study, and our results, confirm the substantial bias in instruments employing an MnCl2 scrubber, a replication of the earlier work with an MnO2 scrubber type and no humidity correction is needed.